A novel role for Beta-adrenergic receptor in mammary branching morphogenesis and its implication in breast cancer - Gargiulo, Lucía (2016)
The mammary gland develops from embryogenesis to infancy-puberty and adulthood, by the input of circulating hormones. At birth the gland is composed of a rudimentary ductal system that grows allometrically until puberty (4-weeks in mice). Later on, estrogens, growth hormone and insulin like growth factor induce expansive proliferation[...].